Optimisation of biolubricant synthesis from castor–maggot oil mixture via two-stage transesterification using response surface methodology - Teuku Mukhriza; Adelia Yesya Putri Hasibuan; Erna Juwita; Husni Husin; Arridina Susan Silitonga (Jurnal Polimesin, 2026)
This study investigates the optimisation and characterisation of a biolubricant produced from a castor–maggot oil mixture via two-stage transesterification. Response surface methodology using a Box–Behnken design was employed to optimise the oil volume ratio, catalyst concentration, and reaction time. The optimum conditions were a castor oil–maggot oil ratio of 50% (v/v), a catalyst concentration of 1% (w/w), and a reaction time of 2 h, resulting in a biolubricant yield of 71.43%. Ethylene vinyl acetate and ethyl-cellulose were added to enhance stability and performance. The biolubricant exhibited a viscosity index of 101.88, kinematic viscosity at 40°C of 54.57 cSt, and a flash point of 235°C, complying with ISO VG 68 and SNI 7069.9:2016 standards. These performance characteristics demonstrate favourable viscosity–temperature behaviour, adequate thermal safety, and suitability for industrial lubrication systems. The integration of mixed vegetable–insect oil feedstocks with Response Surface Methodology (RSM)–Box–Behnken optimisation, together with the incorporation of performance-enhancing additives, resulted in a biodegradable, non-toxic, and environmentally friendly biolubricant that meets standard requirements and shows strong potential as a sustainable alternative to petroleum-based lubricants for mechanical applications.